PRECARIOUSNESS, GENDER AND RACIALITY: work experiences in Brazil and Portugal - Estanque, Elísio; Barbosa, Agnaldo Sousa [UNESP]; Vannuchi, Maria Lúcia; Mendes, Alexandre Marques [UNESP] (Universidade Federal da Bahia, 2024)
This article presents a brief portrait that illustrates some of the contours of precarious lives structured through work. Here we look at elements of struggle and subjectivities accommodated to the ways of life and forms of adaptation that global capitalism promotes and reproduces. The three cases analysed – Franca-SP; São João da Madeira, Portugal; and the domestic workers sector in Salvador-BA – illustrate different realities, but they mirror forms of acceptance and precariousness structured by modes of domination and oppression linked to the same neoliberal economic system. The subordinate condition to which these segments have been consigned reflects complex combinations of factors, where class, race and gender come together, with the strength of each of them fluctuating according to each case. While racial and gender discrimination are more evident in the case of domestic workers, class dimensions combined with consent subjectivities and identities were stronger in the footwear industry.
PRÉCARITÉ, GENRE ET RACIALITÉ: expériences de travail au Brésil et au Portugal
PRECARIEDADE, GÊNERO E RACIALIDADE: experiências de trabalho no Brasil e em Portugal
Keywords: Domestic workers; Footwear industry; Precariousness; Race